Perbedaan Prestasi Belajar Matematika melalui Model Pembelajaran Jigsaw Dan Two Stay Two Stray Dengan Kemampuan Awal Di Sma Negeri 1 Terbanggi Besar - Tri Indah Utami (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2018)
The difference of students achievement in mathematics by using jigsaw and two stay two stray model learning with entry behavior at SMA N 1 Terbanggi Besar Lampung Tengah. The objectives of this research are to describe : 1) the interaction between learning and entry behavior on student’s achievement, 2)the difference of students achievement between Jigsaw and TSTS model learning, 3)the difference of students achievement through Jigsaw and TSTS model learning for high entry behavior students, 4)the difference of students achievement through Jigsaw and TSTS model learning for low entry behavior students. The method used is experimental research. The population of the research was conducted at two classes with the samples of students class X IPA 2 and X IPA 6 in SMA N I Terbanggi Besar Central Lampung , involving 64 students.The data collecting was done by using test instrument. Then the data analysis used variant analysis with two directions and T-test. The research results show that : (1) there is an interaction of student’s achievement between learning and their entry behavior with P-value of 0,036, (2) the average student’s achievement who use Jigsaw model learning is higher than TSTS model learning with average difference of 1,94 and P-value 0,024,(3) the average achievement on high entry behavior students who use Jigsaw model learning is higher than TSTS model learning with the average difference of 5,14 and P-value 0,045, (4) there is no differenceon the average achievement on low entry behavior studens who use Jigsaw and TSTS model learning with P-value of 0,852.